CD3 expression distinguishes two γδT cell receptor subsets with different phenotype and effector function in tuberculous pleurisy - Yokobori, Noemí (2009)
Summary Tuberculous pleurisy is a naturally occurring site of Mycobacterium tuberculosis (Mtb) infection. Herein, we describe the expression of activation, natural killer (NK) and cell migration markers, as well as effector functions from γδT cells in peripheral blood (PB) and pleural effusion (PE) from tuberculosis patients (TB). We observed a decreased percentage of circulating γδT from TB patients and differential expression of NK as well as of chemokine receptors on PB and PE. Two subsets of γδT cells were differentiated by the CD3/γδT cell receptor (γδTCR) complex. The γδTCRlow subset had a higher CD3 to TCR ratio and was enriched in Vδ2+ cells, whereas most Vδ1+ cells belonged to the γδTCR high subset. In PB from TB, most γδTCRhigh were CD45RA+CCR7- and γδTCRlow were CD45RA+/-CCR7+CXCR3+. In the pleural space the proportion of CD45RA-CCR7+CXCR3+ cells was higher. Neither spontaneous nor Mtb-induced interferon (IFN)-γ production was observed in PB-γδT cells from TB; however, PE-γδT cells showed a strong response. Both PB- and PE-γδ T cells expressed surface CD107a upon stimulation with Mtb. Notably, PE-γδTCR low cells were the most potent effector cells. Thus, γδT cells from PB would acquire a further activated phenotype within the site of Mtb infection and exert full effector functions. As γδT cells produce IFN-γ within the pleural space, they would be expected to play a beneficial role in tuberculous pleurisy by helping to maintain a T helper type 1 profile. © 2009 British Society for Immunology.